WORKSHOP PEMBUATAN HANDOUT DAN PENDAMPINGAN GURU DALAM PROGRAM OLIMPIADE DI SMK MUHAMMADIYAH 2 MALANG - Siti Khoiruli Ummah; Alfiani Athma PutriRosyadi; Reni Dwi Susanti; Mayang Dintarini (Jurnal Pendidik Indonesia (JPIn), 2018)
The purpose of the workshop is making handouts in the level of Mathematical Olympiad for student in Vocational School (SMK). The implementation of the workshop and mentoring Olympiad is in SMK Muhammadiyah Malang 2. Stages of devotion in the form of workshop activities include: 1) socialization of mathematical Olympiads, 2) workshop 3 handout) making accompaniment the creation of material handouts, and 4) trials handouts on students. The results of the workshop in the form of handouts mathematical Olympiads CMS trial results and handouts to the students of SMK.